Retour à la forme et au fond du récit : pour une pratique de la motivation littéraire - Hans Färnlöf (Cahiers de Narratologie)
The notion of literary motivation, defined by the Russian formalists as motivirovka, opens up important perspectives for literary studies owing to its dual function. Ensuring the progression of the story by establishing connections between the elements in the storyworld, literary motivation also refers to the way in which this narrative arrangement obeys a poetic purpose on the compositional level. Depending on the weight given to these two aspects, the study of motivation could highlight the image of reality given by the text just as well as accentuate the fictionality of the text as a work of art. The external and internal fields of reference upon which are based the motivations in the storyworld also influences the analysis of the text. Provided that its use is not limited to indicate the degree of verisimilitude of the story, literary motivation can, thanks to its different possible applications, become a particularly powerful methodological tool, capable of exploring any narrative or drama.